The Function of Islamic Law to Develop the Economy in Indonesia - Nasution, Suherman; Nasution, Ramadhany (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2022)
Islamic financial matters is as of now a monetary framework that is extremely popular even by Muslims even created nations, which recognizes it from other financial frameworks is off-base the other is the wellspring of regulation that underlies all monetary action, and the fundamentals of other Islamic legitimate way of thinking that shapes the reason for the improvement of Islamic financial aspects anyplace and in any structure, and should not be out of the passage of sharia. Benefit is the principal objective in Islamic financial action and avoid everything type of damage. Through this paper with subjective exploration techniques, with standardizing juridical methodology through writing study. So with this technique philosophical qualities in the advancement of Islamic financial aspects in Indonesia can be investigated